Fighting female genital mutilation/cutting (FGM/C): towards the endgame and beyond - Saidou Sabi Boun; Akaninyene Otu; Sanni Yaya (BMC, 2023)
Abstract Despite the criminalization of the practice by numerous laws and international treaties in most countries concerned, female genital mutilation/cutting (FGM/C), although on the decline overall, is stagnating or tending to increase in some parts Africa. This relative failure in the fight against FGM/C could be explained from an institutional perspective. Although these struggles affect the regulatory mechanisms, which include laws, they hardly touch the normative mechanisms, which constitute the set of values deemed socially acceptable by a society, and the cultural and cognitive mechanisms, which are the manifestations of the ideologies or beliefs of a group. The naming of FGM/C among certain ethnic groups, which is part of the normative character of the social institution, rather valorizes them and makes uncut girls/women feel "dirty" or "unfit". In these communities, women who have undergone FGM/C are viewed by society as women of honour while uncut girls are perceived as promiscuous and victims of mockery, rejection, or exclusion by the community. In addition, since excision ceremonies and rituals are exclusively reserved for women, many see them as a way of freeing themselves from the rules of patriarchy and male domination that are omnipresent in the societies concerned. Informal mechanisms such as the use of witchcraft, gossip, and beliefs related to the supernatural power of the excisors underpin the cultural-cognitive nature of FGM/C practice. As a result, many families are reluctant to challenge the cutters. The fight against FGM/C can be more effective by addressing the normative and cultural-cognitive roots that form the basis for its perpetuation. This can be achieved by avoiding moralizing the practice, involving those who resist the practice in a context of high prevalence, known as "positive deviants," and using productive methods from the societies concerned. This will create a social environment in which FGM/C is increasingly perceived as less favourable and will ultimately allow for a gradual reform of the normative and cultural-cognitive character of societies that practice FGM/C. Education of women and social mobilisation are critical tools which can act as powerful levers in shifting attitudes about FGM/C.